Effect Of Adding Probiotics Sachet In Standard Formula Feed On Prevention Of Necrotizing Enterocolitis In Preterm Babies - Samia Mehmood, Asima Khanam, Nighat Jabeen, Saira Arshad, Rabia Aziz, Adeela Aftab (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Annually 15 million babies are born prematurely throughout the world and ofwhich 1 million die due to complications related to prematurity; necrotizing enerocolitis (NEC) being one of them. Objective